2015
DOI: 10.1073/pnas.1515966112
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin systems mark pathogen-containing vacuoles as targets for host defense by guanylate binding proteins

Abstract: Many microbes create and maintain pathogen-containing vacuoles (PVs) as an intracellular niche permissive for microbial growth and survival. The destruction of PVs by IFNγ-inducible guanylate binding protein (GBP) and immunity-related GTPase (IRG) host proteins is central to a successful immune response directed against numerous PV-resident pathogens. However, the mechanism by which IRGs and GBPs cooperatively detect and destroy PVs is unclear. We find that host cell priming with IFNγ prompts IRG-dependent ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
237
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(259 citation statements)
references
References 68 publications
(104 reference statements)
13
237
2
Order By: Relevance
“…In support of our finding, TRAF6 was found to be translocated into pathogen-containing vacuoles (PVs) (45) and was involved in the ubiquitin-dependent labeling of PVs, which provide a safe haven for many intracellular bacterial pathogens (46). In conclusion, we have described here a mechanism by which S. Typhimurium T3SS effectors broaden their functions through the activation of host proteins in a ubiquitination-dependent manner to modulate host transcriptional responses so as to adapt host cells to the intracellular replication of bacteria.…”
Section: Traf6 Ubiquitination Of Stat3supporting
confidence: 80%
“…In support of our finding, TRAF6 was found to be translocated into pathogen-containing vacuoles (PVs) (45) and was involved in the ubiquitin-dependent labeling of PVs, which provide a safe haven for many intracellular bacterial pathogens (46). In conclusion, we have described here a mechanism by which S. Typhimurium T3SS effectors broaden their functions through the activation of host proteins in a ubiquitination-dependent manner to modulate host transcriptional responses so as to adapt host cells to the intracellular replication of bacteria.…”
Section: Traf6 Ubiquitination Of Stat3supporting
confidence: 80%
“…1E). More detailed studies on the mechanism of GBP binding to C. trachomatis inclusion membranes confirmed these observations (46). Together, these data indicated that C. muridarum barred GBPs from binding to its surrounding inclusion membrane, an activity likely underlying the observed resistance of C. muridarum to GBP-mediated bactericidal or bacteriostatic effects that help eliminate infections with C. trachomatis.…”
Section: Chlamydia Muridarum Is Resistant To Gbp-mediated Cell-autonosupporting
confidence: 52%
“…We previously demonstrated that IRGs are essential for targeting GBPs to Toxoplasma-and Chlamydia-containing vacuoles (20,21). In this study, we describe an IRG-independent pathway by which GBPs are delivered to PVs.…”
Section: Significancementioning
confidence: 70%
“…Although IRGs and GBPs can combat intracellular infections cooperatively, mounting evidence suggests that these two protein families also execute unique cellular functions independent of one another (16). For example, IRGs facilitate the delivery of ubiquitin E3 ligases to Toxoplasma-and Chlamydia-containing vacuoles independent of GBPs (21,22). GBPs, on the contrary, were reported to control the deposition of the NADPH oxidase NOX2 at Mycobacterium-containing phagosomes independent of IRGs (24).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation